Perkembangan Pengaturan Tindak Pidana Perzinaan Di Indonesia - Nufus, Hayatun; Nur Izzati, Halimah (Desiderata Law Review, 2025)
Abstract Criminal law reform is important. The regulation of the crime of adultery is contained in Articles 411-413 of Law Number 1 of 2023 concerning the Criminal Code. The Formulation of the article can be seen as an expansion for perpetrators of adultery, namely that those who are not husband and wife or who are not married can be subject to criminal sanctions and includes an article for people who live together outside of marriage can also be given criminal sanctions. The legal research applied is normative legal research, then the use of the statutory regulatory approach method and the comparative approach to criminal law related to adultery in Malaysia and Brunei Darussalam. The research study provides a perspective related to adultery and the imposition of sanctions in the crime of adultery in the form of imprisonment and fines for perpetrators of adultery, so that with these sanctions it can prevent the occurrence of criminal acts of adultery in Indonesia because it violates the rules of law and the rules that exist and develop in society. Keywords : Development; Regulation; Adultery